Sams teach yourself iOS 8 application development in 24 hours. - Ray, John, 1971- (Sams, 2015)
"iOS 8 Video How-To is a series of short, 2- to 5-minute how-to videos that walk you through a specific task or technique related to iOS 8 application development. Adapted from John Ray's book Sams Teach Yourself iOS 8 Application Development in 24 Hours, each video is self-contained and focused entirely on one particular task. You can either go through the videos in sequence or you can jump into a particular task, see how something is done, and then jump out again."--Resource description page.